Impact of Race and Insurance Status on Primary Treatment for HPV-Associated Oropharyngeal Squamous Cell Carcinoma. (June 2022) - Habib, Andy M.; Carey, Ryan M.; Prasad, Aman; Mady, Leila J.; Shinn, Justin R.; Bur, Andrés M.; Brody, Robert M.; Cannady, Steven B.; Rajasekaran, Karthik; Ibrahim, Said A.; Newman, Jason G.; Brant, Jason A.
Objective: To assess the impact of sociodemographic factors on primary treatment choice (surgery vs radiotherapy) in patients with human papillomavirus–associated (HPV+) oropharyngeal squamous cell carcinoma (OPSCC). Study Design: Retrospective analysis of the National Cancer Database. Setting: Data from >1500 Commission on Cancer institutions (academic and community) via the National Cancer Database. Methods: Our sample consists of patients diagnosed with HPV+ OPSCC from 2010 to 2015. The primary outcome of interest was initial treatment modality: surgery vs radiation. We performed multivariable logistic models to assess the relationship between treatment choice and sociodemographic factors, including sex, race, treatment facility, and insurance status. Results: Of the 16, 043 patients identified, 5894 (36.7%) underwent primary surgery while 10, 149 (63.3%) received primary radiotherapy. Black patients were less likely than White patients to receive primary surgery (odds ratio [OR], 0.80; 95% CI, 0.66-0.96). When compared with privately insured patients, those who were uninsured or on Medicaid or Medicare were also less likely to receive primary surgery (OR, 0.70 [95% CI, 0.56-0.86]; OR, 0.77 [95% CI, 0.65-0.91]; OR, 0.85 [95% CI, 0.75-0.96], respectively). Patients receiving treatment at an academic/research cancer program were more likely to undergo primary surgery than those treated at comprehensive community cancer programs (OR, 1.33; 95% CI, 1.14-1.56). Conclusion: In this large sample of patients with HPV+ OPSCC, race and insurance status affect primary treatment choice. Specifically, Black and nonprivately insured patients are less likely to receive primary surgery as compared with White or privately insured patients. Our findings illuminate potential disparities in HPV+ OPSCC treatment.